High subcutaneous adipose tissue density correlates negatively with survival in patients with hepatocellular carcinoma. (18th December 2020) - von Hessen, Leona; Roumet, Marie; Maurer, Martin Helmut; Lange, Naomi; Reeves, Helen; Dufour, Jean‐François; Radu, Pompilia
Abstract: Background & Aims: Body composition parameters have been reported to add information, which can lead to tailored treatment and prognostication for oncological patients. Data for patients with hepatocellular carcinoma (HCC) are scarce. We assessed the association between different body composition parameters and overall survival (OS) in two different newly diagnosed HCC populations. Methods: The area (cm 2 ) and density (Hounsfield Units [HU]) of skeletal muscle (SM) and adipose tissue (subcutaneous [SAT], visceral [VAT] and intermuscular [IMAT]) were measured on computed tomography (CT) scans at the level of the third lumbar vertebra (L3) in two cohorts of patients diagnosed in different HCC stages (Bern, Switzerland n = 187 and Newcastle, United Kingdom n = 216). Univariate and multivariate Cox regressions analyses were used to assess the crude and adjusted association of body composition parameters with OS. Results: By univariate analysis, in both cohorts, Bern and Newcastle, high SAT density (hazard ratio [HR]: 1.35; 1.12‐1.62, P  < .001 and 1.44; 1.27‐1.63, P  < .001, respectively) and high VAT density (HR: 1.38; 1.1‐1.72, P  = .005 and HR: 1.53; 1.3‐1.81, P  < .001, respectively) correlated negatively with survival. After model adjustment for potential baseline confounders (gender, age, diabetes, cirrhosis, MELD score, BCLC stage) in a multivariate analysis, SAT density remained associated with mortality in Bern and Newcastle (Bern: HR: 1.27; 1.04‐1.57, P  = .022; Newcastle: HR: 1.23; 1.03‐1.48, P  = .022) and VAT remained associated with mortality in Bern (HR: 1.31; 1.05‐1.65, P  = .019). Conclusions: Based on two HCC cohorts, our data show that high SAT density correlates negatively with OS in HCC patients.